Bilateral swelling self-inflating tissue expanders - Min, X (2022)
Hydrogel tissue expander (HTE) self-inflates in vivo by gradually absorbing body fluid. It eliminates the regular injections required by the conventional balloon-type tissue expander and provides a more progressive stretching process to the tissue. Previously, the hot-compressed anisotropic HTE (A-HTE) has achieved uniaxial swelling and could potentially match defects of anisotropy. This present work applied die-drawing as the solid-state processing to impart shape memory to the crosslinked copolymer of N-vinyl-pyrrolidone and methyl methacrylate, poly(VP-MMA) and successfully produced a novel self-inflating tissue expander with bilateral swelling properties.